1992
DOI: 10.1002/ctpp.2150320604
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence of the Mean Electron Energy in the Bulk Plasma of an RF Discharge in Argon

Abstract: The pressure dependence of the mean electron energy ( E ) was investigated in discharges in Ar experimentally by sampling the plasma potential with an ion mass spectrometer, and theoretically by solving the electron Boltzmann equation for the bulk plasma. Both results show a decrease in ( E ) with increasing pressure in the regime between 0.2 and 40 Pa although this behaviour is much more pronounced in the experimental results. The results are compared to those of single-probe measurements of other authors.In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Non-isothermal plasmas interact with organic substrates via a direct energy transfer component arising from ions and metastables down to /'-10 A, and a radiative transfer component consisting of vacuum ultraviolet (VUV) photo-irradiation which can penetrate up to ~10 nm below a polymer surface.30-32 Typically, ion densities lie in the range 108-1010 cm-3 with energies of 0-100 eV,33-36 while mean electron energies (e) span 0-20 eV with a high-energy tail reaching out to 100 eV due to reflections at sheath boundaries. 33,37 Within the glow region, the plasma exists at a positive potential with respect to the substrate surface; this results in positive ions contained in the plasma being accelerated through a space charge sheath toward the substrate.38…”
Section: Discussionmentioning
confidence: 99%
“…Non-isothermal plasmas interact with organic substrates via a direct energy transfer component arising from ions and metastables down to /'-10 A, and a radiative transfer component consisting of vacuum ultraviolet (VUV) photo-irradiation which can penetrate up to ~10 nm below a polymer surface.30-32 Typically, ion densities lie in the range 108-1010 cm-3 with energies of 0-100 eV,33-36 while mean electron energies (e) span 0-20 eV with a high-energy tail reaching out to 100 eV due to reflections at sheath boundaries. 33,37 Within the glow region, the plasma exists at a positive potential with respect to the substrate surface; this results in positive ions contained in the plasma being accelerated through a space charge sheath toward the substrate.38…”
Section: Discussionmentioning
confidence: 99%
“…Inert gas plasmas interact with organic substrates via a direct energy transfer component arising from ions and metastables down to ~10 A, and a radiative transfer component consisting of vacuum ultraviolet (VUV) photoirradiation which can penetrate up to ~10 nm below a polymer surface.27-29 Typically, ion densities lie in the range 108-1010 cm-3 with energies of 0-100 eV,30-33 while mean electron energies (e) span 0-20 e V with a high energy tail reaching out to 100 eV due to reflections at sheath boundaries. [30][31][32][33][34] Crossed-beam electron impact induced fluorescence studies with argon atoms have shown that the most intense VUV emission lines appear at 104.8 and 106.7 nm; these give rise to the Ar I transitions between the lowest lying electronically excited states and the ground state of the atom (i.e. 3s23p54sx -3s23p6).35 '36 The excited ion Ar II resonance lines at 91.98 and 93.21 nm also emit strongly and correspond to the 3sx3p6 -* 3s23p5 transitions.…”
Section: Discussionmentioning
confidence: 99%
“…4(b) for p = 25 mTorr and p = 40 mTorr]. 23 The different IEDs at the various pressure levels directly affect the etching features. For instance, at low pressure ( p = 5 mTorr) the F and C radical densities are relatively low, 24 while the ion energy is the highest between the investigated pressure levels.…”
Section: B Effect Of the Pressure And Ion Energy Distributionmentioning
confidence: 99%